EKSISTENSI KERIS JAWA DALAM KAJIAN BUDAYA - Kuntadi Kuntadi (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2019)
AbstractKeris as a cultural product whose existence in addition has a beauty value is also loaded with meaning and function that are so important in society. Kris is a masterpiece of indigenous Indonesian cultural heritage that has a beautiful and unique form. So that the kris has been recognized as the World Heritage of Humanity from the world body, UNESCO.The main objective of this research is to find out the description of the existence and development of Javanese kris through a cultural perspective. This research is qualitative research, to reveal the existence of Javanese kris in a cultural context using qualitative interactive analysis with hegomoni and constructive approaches.The results of this study are the discovery of two categories of Javanese kris, namely: tangguh kris, with the concept of working on mutrani, and kamardikan kris, where artists / masters in free work are not bound by the hegemony of the king’s power, they have an ideology by prioritizing creativity as self-expressionKeywords: kris, culture, tangguh and kamardikanAbstrakKeris sebagai produk budaya keberadaannya di samping memiliki nilai keindahan juga sarat dengan makna dan fungsi yang begitu penting dalam masyarakat. Keris merupakan karya agung warisan budaya asli Indonesia yang memiliki bentuk indah dan uniq. Sehingga keris telah diakui sebagai World Heritage of Humanity dari badan dunia yaitu UNESCO.Tujuan utama penelitian ini adalah untuk mengetahui gambara tentang eksistensi dan perkembangannya keris Jawa melalui perspektif budaya. Penelitian ini merupakan penelitian kualitatif, untuk mengungkap eksistensi keris Jawa dalam konteks budaya menggunakan analisis interaktif kualitatif dengan pendekatan hegomoni dan deskontruksi.Hasil penelitian ini adalah ditemukannya dua kategori keris Jawa yakni: keris tangguh, dengan konsep garap mutrani, dan keris kamardikan, dimana seniman/empu dalam kekaryaan bebas tidak terikat oleh hegomoni kekuasaan raja, mereka dalam berkarya memiliki idiologi dengan lebih mengutamakan kreativitas sebagai ungkapan aktuali diri.Kata Kunci: keris, budaya, tangguh dan kamardikan